1999
DOI: 10.1159/000028085
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Necrotic or Apoptotic Cell Uptake on Antigen Presentation by Macrophages

Abstract: The induction of pathogenic immune responses may be dependent on the immune system receiving ‘danger’ signals resulting from tissue damage, rather than tolerogenic stimuli associated with normal cell turnover. The aim was to test this hypothesis by comparing the effects of the uptake of necrotic and apoptotic cells on the ability of antigen-presenting cells (APC) to stimulate immune responses in vitro. The experiments focused on presentation by the macrophage, which is the main cell type adapted for clearing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 2 publications
2
39
0
Order By: Relevance
“…Voll et al (24) demonstrated that addition of apoptotic lymphocytes to endotoxin-stimulated PBMC caused a shift from secretion of proinflammatory cytokines (TNF-␣, IL-1␤, and IL-12) to antiinflammatory cytokines (IL-10). Barker et al (25) showed that macrophages that ingested apoptotic cells had increased FIGURE 5. A, Comparison between septic and trauma for lymphoid follicles and total B cell area based on the duration of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Voll et al (24) demonstrated that addition of apoptotic lymphocytes to endotoxin-stimulated PBMC caused a shift from secretion of proinflammatory cytokines (TNF-␣, IL-1␤, and IL-12) to antiinflammatory cytokines (IL-10). Barker et al (25) showed that macrophages that ingested apoptotic cells had increased FIGURE 5. A, Comparison between septic and trauma for lymphoid follicles and total B cell area based on the duration of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that such macrophages ingesting apoptotic cells not only fail to induce inflammation but also actively suppress an inflammatory immune response (Fadok et al, 1998(Fadok et al, , 2000. Macrophages with ingested apoptotic cells markedly decrease expression of CD40, a co-stimulatory factor for T-lymphocytes (Barker et al, 1999) of proinflammatory cytokines and increased production of prostaglandin E2 and transforming growth factor-b1 (Fadok et al, 1998), both factors involved as regulators of physiological T cell homeostasis, activation, differentiation, and effector function. Recently, it has been shown that cells of a macrophage cell-line cocultured with AM only underwent apoptosis when activated with IFN-γ, while apoptosis was not found when IFN-γ was absent (Li et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…43 One possibility in our colitis model is that exogenous OPN may contribute to the termination of inflammation by activating macrophages to take up apoptotic neutrophils, thereby leading to neutrophil clearance and the release of anti-inflammatory and reparative cytokines, such as TGF-b1. 44 Both in vitro and in vivo evidence suggest that secretion of TGF-b1 by macrophages can suppress pro-inflammatory signaling from Tolllike receptors, further stimulating tissue repair. 45,46 The attenuation of an inflammatory reaction coincides with the departure of macrophages through the lymphatics.…”
Section: Bovine Milk Opn Decreases Destructive Capacity Of Neutrophilmentioning
confidence: 99%